PERFORMANCE OF THE AMORPHOUS SOLAR CELL IN THE MALAYSIAN CLIMATE - Mohd Hafiidz Jaafar (Fakulti Sains dan Teknologi, 2012)
This study focuses on the performance of the amorphous solar cell in the Malaysian climate. The purpose of this study is to determine the efficiency of the amorphous solar cell of the chosen angles of 10° and 20°, and to study the relations of these efficiencies with the weather parameters that have been chosen which are the intensity, wind speed, relative humidity and temperature.